Phonon-assisted anti-Stokes excitation of the fluorescence of Mn2+ ions in the CsMnCl3 ּ 2H2O crystal - Eremenko, V. V.; Fomin, V. I.; Kurnosov, V. S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
We demonstrate that anti-Stokes excitation of Mn2+ ions in CsMnCl3ּ2H2O crystal is possible through multi-phonon addition to the energy of the photons of exciting light. The deficit dE between the energyof the Mn2+ 4T1 exciton and the photon energy of the He√Ne laser used as the source of illumination is compensated by simultaneous annihilation of several thermally activated lattice phonons. The absence of two-photon activation of the fluorescence was verified by measurement of the dependence of the fluorescence intensity on the intensity of the exciting light, which appears linear at fixed energy mismatch dE.